Antibacterial Activity of Defatted Ethanolic Extract of Cordyline fruticosa (L.) A.Chev Leaves Against Respiratory Pathogen - Vera Nurviana; Eka Indriyani; Ira Rahmiyani (JSFK (Jurnal Sains Farmasi & Klinis), 2026)
Introduction: Red hanjuang (Cordyline fruticosa L.) leaves have traditionally been used to treat respiratory tract infections, including productive cough caused by Staphylococcus aureus. The increasing prevalence of antibiotic resistance highlights the need for natural antibacterial agents. Objective: This study aimed to evaluate the antibacterial activity of the 70% ethanol extract of red hanjuang leaves against S. aureus. Methods: Leaves were dried, powdered, and extracted through maceration with 70% ethanol after defatting with n-hexane. Physicochemical and phytochemical analyses were performed. Antibacterial activity was assessed via the well diffusion method, measuring inhibition zones and determination of the Minimum Inhibitory Concentration (MIC). Data were analyzed with SPSS (p < 0.05). Results: The simplicia met quality standards. Phytochemical screening revealed flavonoids, polyphenols, tannins, and saponins. All extract concentrations (5%, 20%, 35%, 50%) inhibited bacterial growth, with the largest inhibition zone at 50% (16.45 mm). Amoxicillin (positive control) produced 12.826 mm, while DMSO showed no inhibition. The MIC was 0.7% with an inhibition zone of 1.83 mm. Statistical analysis confirmed significant differences among concentrations. Conclusion: The 70% ethanol extract of red hanjuang leaves demonstrated strong antibacterial activity against S. aureus, supporting its potential as a natural therapeutic option for respiratory tract infections